PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DENGAN MODERASI MOTIVASI Studi pada Komisi Pemilihan Umum Kabupaten Grobogan - Joko, Nugroho; Titiek, Suwarti (Jurnal Ilmiah Telaah Manajemen, 2005)
The objective of this research is to examine the impact of leadership style to the job satisfaction with motivation being a moderating variable. This research is case study at KPU (General Election Commission) in Grobogan Regency. By using the purposive sampling method the research finds that leadership style significantly positive impact the job satisfaction with coefficient 0,802. That impact is moderated by job motivation. Keywords : Leadership style, job satisfaction, motivation